Hubungan Antara Pengetahuan dengan Kejadian Kecelakaan Kerja Pada Pekerja Bengkel Las: Kajian Literatur - Siti Khadijah; Anggi Febrian; Keysha Febri Dhanty; Sri Hajijah Purba (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The number of workplace accidents in Indonesia continues to increase every year. In 2019, there were 210,789 cases of workplace accidents, which rose to 221,740 cases in 2020, and further increased to 234,370 cases in 2021. The welding process involves various risks of workplace accidents that may occur at different stages. Starting from selecting and moving products, workers can be scratched by materials or even hit by them. The purpose of this research is to determine whether there is a relationship between knowledge and workplace accidents among welding workshop workers using a qualitative method. Conclusion: There is a significant correlation between an individual's knowledge of Occupational Health and Safety (OHS) practices and their performance in the work environment. The better the welders' knowledge of OHS, in terms of basic knowledge, understanding of concepts, and application in the field, the lower the risk of workplace accidents.